Practising public scholarship: experiences and possibilities beyond the academy - Mitchell, Katharyne (Antipode book series, 2008)
"This book provides a collection of 20 chapters describing the journey to public scholarship. It is a cross-disciplinary exploration of the pleasures and perils associated with breaching the town-gown divide. The contributors come from a variety of departments including geography, comparative literature, sociology, communications, history, and biology and are involved in widely disparate ventures outside of the universities. What unites this incongruent crew is their effort to reach beyond the academy and to make their ideas and research broadly accessible." "Pulling in those people and concepts often ignored in normative academic settings, this book opens the way for a new kind of democratic politics - one based on grounded concepts and meaningful social participation. The chapters are personal biographies which, taken together, provide a broad prescription for social change, both within and outside the university."--Provided by publisher